A policy paradox: why gender equity is men's work. Issue 7 (2nd October 2020) - Anicha, Cali L.; Bilen-Green, Canan; Green, Roger
ABSTRACT: Even in contexts of gender parity, people who identify as men comprise a modest to bare majority; in administrative and other leadership positions, men comprise a broad majority and are thereby unavoidably a plurality of those involved in diversity, equity, and inclusion centred policy change efforts. Paradoxically, men's advocacy for gender-equity often unintentionally conveys gendered biases. We therefore assert that the development of conscientização or critical consciousness in people who identify as men must be explicitly addressed if policies and practices are to be effectively transformed to achieve gender equity. That is, men must come to the recognition that their own best interests are served by the unravelling of gendered systems where unearned over-advantaging for men abounds.